2021
DOI: 10.1016/j.heliyon.2021.e07294
|View full text |Cite
|
Sign up to set email alerts
|

Trust-based fault detection and robust fault-tolerant control of uncertain cyber-physical systems against time-delay injection attacks

Abstract: Control systems need to be able to operate under uncertainty and especially under attacks. To address such challenges, this paper formulates the solution of robust control for uncertain systems under time-varying and unknown time-delay attacks in cyber-physical systems (CPSs). A novel control method able to deal with thwart time-delay attacks on closed-loop control systems is proposed. Using a descriptor model and an appropriate Lyapunov functional, sufficient conditions for closed-loop stability are derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Specifically, some types of deception attacks occur regularly in industrial CPSs. These common attacks include false-data injection attacks in which the generated false data (noise) from the attacker is injected into the communication network to decrease the system's data authenticity, replay attacks in which the previous time data packets are stored and sent repeatedly to prevent the subsystems from reaching the steady-state phase [10], and time-delay attacks in which a delay parameter is injected to the system to cause instability in system's operation [11,12]. Recently, authors in [13] developed a model-free reinforcement learning algorithm to control CPSs under time-delay attacks from a robust perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, some types of deception attacks occur regularly in industrial CPSs. These common attacks include false-data injection attacks in which the generated false data (noise) from the attacker is injected into the communication network to decrease the system's data authenticity, replay attacks in which the previous time data packets are stored and sent repeatedly to prevent the subsystems from reaching the steady-state phase [10], and time-delay attacks in which a delay parameter is injected to the system to cause instability in system's operation [11,12]. Recently, authors in [13] developed a model-free reinforcement learning algorithm to control CPSs under time-delay attacks from a robust perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The K–L measure is effective in detecting attacks with Gaussian distributions in higher‐order linear/non‐linear CPSs [26]. Additionally, correlation analysis is reviewed as another attack detection framework in [12] and its performance is compared with the K–L divergence criterion in real‐time false‐data detection scenarios. During our research on CPSs, we observed that by considering non‐Gaussian signals injected into the system in the form of time delays or injected false data, the system's performance degraded significantly while the malicious signals remained stealthy.…”
Section: Introductionmentioning
confidence: 99%